Analysis of Contradictory Messages in Advertisements (Semiotic Analysis of Citra Advertisement Version “Pancarkan Ragam Cantik Kulit Indonesia”) - Alfano Utomo; Merry Fridha Tripalupi; Irmasanthi Danadharta (LONTAR: Jurnal Ilmu Komunikasi, 2025)
In the advertising industry, the media plays an important role in shaping public perceptions of beauty standards, including in Indonesia. Representations of women in advertisements are often depicted with ideal images centered on fair skin. Although advertisements now often feature representations of diversity, these standards are still made subtly in the media. This study discusses the contradictory messages contained in the Citra advertisement version “Pancarkan Ragam Cantik Kulit Indonesia” using Charles Sanders Peirce's semiotic method. This research is a qualitative study using a constructivism paradigm approach with text analysis. The purpose of this study is to uncover the hidden meanings in advertisements using Charles Sanders Peirce's semiotic method with Jacques Derrida's deconstruction theory. The results of the study show contradictory messages in the representation of diversity raised in this advertisement. Although Citra highlights the diversity of Indonesian skin color beauty, the presence of visuals such as placing light-skinned women as the main focus, the use of skin lightening ingredients such as bengkuang and niacinamide in Citra products as the main selling point, animations of skin color changes towards lighter, the appearance of characters who have dark skin characters with the label "Glowing Skin" still refers to the standard of beauty of light skin. This advertisement has not completely deconstructed the standard of beauty, but rather reproduces it in a new and more subtle form in selling its products.